2019
DOI: 10.1088/1748-9326/ab4d71
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the water-use reduction associated with the transition from coal to natural gas in the US electricity sector

Abstract: The transition from coal to natural gas and renewables in the electricity sector and the rise of unconventional shale gas extraction are likely to affect water usage throughout the US. While new natural-gas power plants use less water than coal-fired power plants, shale gas extraction through hydraulic fracturing has increased water utilization and intensity. We integrated water and energy use data to quantify the intensity of water use in the US throughout the electricity's lifecycle. We show that in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Most of the attention has been focused on receiving climate and air quality benefits by switching from coal‐fired electricity to greener energy production. The amount of water required for coal‐fired electricity production could be saved by the transition to solar or wind energy which results in the saving of billions of gallons of water (Kondash, Patino‐Echeverri, & Vengosh, 2019). It was reported that every megawatt of electricity produced from renewable sources instead of coal saves 10,500 gal of groundwater.…”
Section: Policy For Bangladeshʼs Energy Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the attention has been focused on receiving climate and air quality benefits by switching from coal‐fired electricity to greener energy production. The amount of water required for coal‐fired electricity production could be saved by the transition to solar or wind energy which results in the saving of billions of gallons of water (Kondash, Patino‐Echeverri, & Vengosh, 2019). It was reported that every megawatt of electricity produced from renewable sources instead of coal saves 10,500 gal of groundwater.…”
Section: Policy For Bangladeshʼs Energy Transitionmentioning
confidence: 99%
“…One way of achieving this is to encourage people to set up solar systems on their roofs and to enable people to sell their excess electricity to the national grid at specific tariffs. It was reported that roofs hold gigantic solar potential in Bangladesh to produce 1,000 MW of power (Kondash et al, 2019).…”
Section: Policy For Bangladeshʼs Energy Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand these interactions among water and energy, scholars have evaluated the amount of energy needed to produce water and conversely the amount of water needed to produce energy across different types of water and energy infrastructure (Gleick, 1994; Kondash, Patino‐Echeverri, & Vengosh, 2019; Mekonnen, Gerbens‐Leenes, & Hoekstra, 2015; Siddiqi & Anadon, 2011). Siddiqi and Anadon (2011) show through a country‐level quantitative assessment of the water‐energy nexus that water infrastructure in many parts of the MENA depends heavily on energy, in contrast to a relatively weak dependence of energy systems on fresh water.…”
Section: The Water‐energy Nexus and Infrastructurementioning
confidence: 99%
“…When it comes to the water footprint for energy consumption in the MENA, many countries depend upon natural gas and oil to generate electricity (Mekonnen et al, 2015). After coal and nuclear, oil and natural gas have the next highest lifecycle water withdrawal intensity of electricity generation, while wind and solar power have lower water footprints (Kondash et al, 2019).…”
Section: The Water‐energy Nexus and Infrastructurementioning
confidence: 99%